(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Imagining people’s functions in everyday life and work without ICT seems complicated. Since it substantially ensures the competitiveness of different systems at the micro and macro levels, its application is ubiquitous, regardless of the aspect from which it is observed. Numerous national and multinational strategies try to encourage educational systems, focusing on ICT to acquire skills, competencies and knowledge more effectively. This should represent added value to all future generations. This article emphasizes the structural approach to market divergence, and it analyzes the representation of the ICT development index (ICT) in European countries that compares a set of Scandinavian countries and other European Union countries. It is known that Scandinavian countries belong to those countries that have recognized the importance of involving ICT in educational programs, which improves the economy of a particular selected country. Considering this, the research reveals how ICT is essential in improving socio-economic development in many countries.